Penerapan Media Pembelajaran Berbantuan Geogebra untuk Memecahkan Masalah Meteri Transformasi - Nazihah, Ulfatun; Susanto, Susanto; Abi Suwito (Pendidikan Matematika FKIP Universitas Mataram, 2023)
Students’ difficulties in solving students' integral questions are caused by students enable to visualize abstract transformations. The lack of media used causes students to have difficulties in solving transformation. One of the alternatives to overcome this problem is by using GeoGebra-assisted learning media Therefore, the purpose of this study was to apply the media and to determine the effect of GeoGebra-assisted media on solving the problem of transformation. This Research engages 27 students. The design used in this study was the One-Group Pretest-Posttest. The data is obtained from the results of the pretest, treatment, and post-test. The data analysis technique used descriptive statistical data analysis technique and statistical inference. From the descriptive statistical analysis technique, the average pretest value was 29.44 and the posttest average was 91.67. From this average, there was an overall increase of 96.30%. The results of the inference analysis using the t-test obtained = 16.39 and = 1.684. this media also received a positive response from students. This can be seen from the student response questionnaire which got a total score of 93.09%. We can conclude that the GeoGebra media is very effectively used to solve the problem of transformation.